Charting new paradigms for CAR-T cell therapy beyond current Achilles heels - Li, Ying; Hu, Zhenhua; Li, Yuanyuan; Wu, Xiaoyan (Frontiers in Immunology, 2024)
Chimeric antigen receptor-T (CAR-T) cell therapy has made remarkable strides in treating hematological malignancies. However, the widespread adoption of CAR-T cell therapy is hindered by several challenges. These include concerns about the long-term and complex manufacturing process, as well as efficacy factors such as tumor antigen escape, CAR-T cell exhaustion, and the immunosuppressive tumor microenvironment.Additionally, safety issues like the risk of secondary cancers post-treatment, on-target off-tumor toxicity, and immune effector responses triggered by CAR-T cells are significant considerations. To address these obstacles, researchers have explored various strategies, including allogeneic universal CAR-T cell development, infusion of non-activated quiescent T cells within a 24-hour period, and in vivo induction of CAR-T cells. This review comprehensively examines the clinical challenges of CAR-T cell therapy and outlines strategies to overcome them, aiming to chart pathways beyond its current Achilles heels.